Kadar Total Suspended Solid pada Air Sungai Nguneng Sebelum dan Sesudah Tercemar Limbah Cair Tahu - Dewi Arum Yuliyanti (Poltekkes Kemenkes Semarang, 2019)
The tofu industry in production process produces liquid waste causing pollution problems, so damaging the environment. Liquid waste tofu contains organic compounds causing high levels of Total Suspended Solid (TSS). Total Suspended Solid (TSS) that settles at the bottom of the river, will form a mud that can disrupt the flow of river water and cause siltation of the river causing siltation of the river. To know the difference of TSS content in Nguneng River water before and after contaminated with tofu waste. Analytical observational research with cross sectional approach. The samples used were Nguneng River water before and after contaminated with tofu waste, then examined TSS levels in duplo with five repetitions based on different days. Data analysis using Paired Sample T-Test with 95% confidence degree. The average TSS levels obtained in Nguneng River water before polluted tofu waste was 220.4 mg / l. The average TSS levels obtained in Nguneng River water after contaminated tofu liquid waste were 558.4 mg / l. Peired Samples T-Test test with 5% error rate and significance of 0 (p 0.05). There is a difference of TSS content in Nguneng River water before and after contaminated with tofu liquid waste.